Parental consent for the Covid-19 vaccine in children. (2nd September 2021) - Power, Andrew
Abstract : Parents may not always agree on childhood immunisation and this may also apply to the Covid-19 vaccination. Dr Andrew Power, Medicolegal Consultant at Medical Protection, discusses how to resolve parental disagreement